P-227 Combined oncology and palliative care clinics; patient place of death. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Russell, Emily; Adami, Lucy; Paterson, Duncan; Gibbins, Jane; Ellis, Richard; Campbell, Carolyn; Newman, Rachel; Stevens, Deborah
Abstract : Background: Combined oncology and palliative care clinics (COPCC) have developed in Cornwall to enable early palliative medicine input into the care of cancer patients. The evidence suggests referrals to palliative care are usually late (Bennett, Ziegler, Allsop, Daniel et al ., 2016), despite growing evidence that earlier palliative care reviews enhance patient quality of life and in some cases survival (Temel, Greer, Muzikansky, Gallagher et al ., 2010). The majority of patients express a preference to die either in their own home or the hospice (Gomes, Higginson, Calanzani, Cohen et al ., 2012; Gao, Ho, Verne, Glickman et al ., 2013; Gomes, Calanzani, Gysels, Hall et al ., 2013), yet unfortunately most die in acute hospitals (Cohen, Pivodic, Miccinesi, Onwuteaka-Philipsen et al ., 2015). The aim of this review was to determine the place of dying phase of care for patients reviewed in the COPCC. Method: A retrospective database review identified place of death for 675 consecutive patients seen in COPCC between 2012 and 2017. Results: 45% died at home or nursing home, 26% died in the hospice and 29% died in hospital (21% acute, 8% community). In comparison nationally, 37% of patients with cancer died at home or nursing home, 17% died in palliative care institutions (i.e. hospice) and 44% died in hospital. Conclusions: COPCC aim to provide holistic palliative care to control symptoms, address information needs, help with psychological distress and guide advance care planning. COPCC allow patients with advanced cancer to be referred earlier to the community palliative care teams or hospice services. Patients who are reviewed in COPCC appear to be more likely to die at home, nursing home or hospice and less likely to die in an acute hospital compared to national data for patients with a cancer diagnosis. COPCC may help patients to die in their preferred place of death. Patients with non-cancer diagnoses such as end stage heart failure may also benefit from combined clinics with palliative care. Further work is needed to explore this.